Improving the Remuneration System of Retail Bank Front-Office Employees - A. S. Artamonov (Управленческие науки)
This article is reviewing PJSC Sberbank’s unique experience in developing and implementing employee incentive programs through the prism of international standards and incentive principles. In the dynamic circumstances of the emerging economy retail segment the employers have to seek the new approaches to compensation system within the framework of the annual payroll budget often with no option to correct it. This restriction requires the holistic approach to run the annual payroll management through building the interrelation between its constant and variable parts. The mentioned interrelation allows to operate flexibly and effectively within given restrictions.One of the ways of its establishment is a line staff incentivizing based on Key Performance Indicators (KPI). The article analyzes the positive and negative sides of this approach, as well as the strategic conditions under which its implementation was justified. As a justification for implementing incentive programs on the basis of KPI the dynamics index of engagement and the staff income satisfaction is provided. The disadvantages of KPI-based incentive system, as well as the ways to change the system based on the opinion of workers and the peculiarities of its administering practice are identified.